MUSEUM-BASED HISTORY LEARNING: RELICS OF THE PRE-LITERACY PERIOD IN INDONESIA IN NORTHERN JAVA AS A LEARNING RESOURCE: Pembelajaran Sejarah Berbasis Museum : Peninggalan Masa Praaksara Indonesia di Jawa Bagian Utara sebagai Sumber Pembelajaran - Hassya, Haris Arifudin Hassya; Ganda, Ganda Febri Kurniawan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
History learning in schools is still dominated by conventional methods such as lectures and memorization, which has an impact on low student participation and the linkage between the material and historical reality. In fact, history is a science that is rich in the value of life if it is conveyed contextually and based on real evidence. Museums as cultural heritage preservation institutions have great potential as an authentic and interactive source of historical learning, especially in conveying historical material during the pre-literacy period. One example is the Patiayam Museum in Central Java, which stores important archaeological relics from the Pleistocene period. However, the use of museums in history learning in schools is still limited due to the lack of integration with the curriculum and the limited resources of teachers. Therefore, this study aims to examine the potential of museums, especially the relics of the preliterate period in the northern part of Java, as a source of contextual, relevant, and meaningful historical learning. The study also highlights the importance of collaboration between schools, governments, and museum managers in supporting learning based on local historical sources. Keywords: Patiayam Museum, Education, Learning Resources